Orally delivered targeted nanotherapeutics for the treatment of colorectal cancer. (2nd June 2020) - Zhang, Xueqing; Song, Heliang; Canup, Brandon S.B.; Xiao, Bo
ABSTRACT: Introduction: Colorectal cancer (CRC), the third-most common malignancy, has high morbidity and mortality. Oral nanotherapeutics have emerged as a promising strategy to improve the therapeutic outcomes and alleviate the adverse effects of drugs in CRC treatment. Areas covered: In this review, we introduce the beneficial features of oral drug administration for CRC therapy, and further address the three basic elements of nanotherapeutics, namely, therapeutic agents, carrier materials, and targeting ligands. In addition, we also discuss the potentials of the new emerging technologies ( e.g ., immunotherapy, gene editing and microbiota manipulation) in the treatment of CRC. Expert opinion: Orally delivered targeted nanotherapeutics represent a promising strategy toward the efficient treatment of CRC. Although the current oral nanotherapeutics exert better therapeutic outcomes than the traditional drug formulations, their application has been restricted by drug resistance, tumor metastasis, and biosafety. Therefore, it is necessary to exploit new nanotherapeutics in the aspects of their three basic elements, and combine the new emerging technologies to those nanotherapeutics for CRC treatment.